The Complexity of the Legal Framework for Regulating the Activity of Tourist Guides in Kosovo - KRASNIQI, Armand; SOJEVA, Diamanta; KUQI, Bekë (Journal of Environmental Management and Tourism, 2023)
In Kosovo, tourism and legislation, despite positive developments for this economic activity, are not at the level of the standards required in the European Union. More specifically, in contrast to other countries, in Kosovo the activity of tourist guides is regulated only within the Law on Tourism and until now no by-laws have been issued to operationalize this specific activity. In the modern conditions of tourism developments, this fact can be one of the obstacles that in reality increases the safety of tourists to visit the tourist resources of our country and produces other negative financial, social, etc. implications. The paper starts from the definition of the term tourist guide, which has also been accepted at the EU level. This model should be the basis of providing a short narrative for the development of the country's tourist guide by analyzing and urgently completing the current legal basis for tourism. The work in a limited way highlights some problematic issues in the beginning and operation of this activity, especially in the sphere of professional certifications and adequate training, including in this direction, the advocacy for the application of the new European standard EN 15565 in Kosovo as well.